LANDASAN YURIDIS TERHADAP ATURAN HUKUM TENTANG PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Baihaqi A Samad (SCAD Independent, 2014)
Construction of Krueng Pase irrigation dams in the village of Pulo Blang, sub-district Meurah Mulia, North Aceh pursuant to Presidential Decree number 65 of 2006 concerning amendments to the Presidential Decree number 36 of 2005 concerning the implementation of land acquisition for the construction of the public interest, is a development in the public interest. Reservoir development Krueng Pase dormant until now, due to delay in land acquisition dam site. Based on the legal analysis to legal facts, it turns out several stages of land acquisition for the construction of irrigation dams Krueng Pase was not conducted in accordance with legal procedures. In land acquisition guess laden with irregularities.